Insentif Pajak Penghasilan pada Lembaga Pendidikan - Intan, Rani (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2016)
The institution of education has a role to realize the vision, mission and goals of the national education system. Therefore, the institution has to be be fully supported by the government through the public policies. In addition to budget 20% of the national budget in the field of education, providing tax incentives to educational institutions is a fresh air for the advancement of education program in Indonesia. With the facilities such as an incentives or tax reduction or tax exemption, the government hopes that the educational instituion will develop the education and learning process thus will ultimately improve the quality of students and human resources in Indonesia in general